Aluminium-catalysed isocyanate trimerization, enhanced by exploiting a dynamic coordination sphere12. Issue 53 (17th June 2019) - Bahili, Mohammed A.; Stokes, Emily C.; Amesbury, Robert C.; Ould, Darren M. C.; Christo, Bashar; Horne, Rhian J.; Kariuki, Benson M.; Stewart, Jack A.; Taylor, Rebekah L.; Williams, P. Andrew; Jones, Matthew D.; Harris, Kenneth D. M.; et al.
Abstract : The lability of aluminium is exploited to give a highly effective catalyst for the trimerization of isocyanates. Abstract : Main-group metals are inherently labile, hindering their use in catalysis. We exploit this lability in the synthesis of isocyanurates. For the first time we report a highly active catalyst that trimerizes alkyl, allyl and aryl isocyanates, and di-isocyanates, with low catalyst loadings under mild conditions, using a hemi-labile aluminium-pyridyl-bis(iminophenolate) complex.